2018
DOI: 10.3390/app8122365
|View full text |Cite
|
Sign up to set email alerts
|

Defect Detection of Aluminum Alloy Wheels in Radiography Images Using Adaptive Threshold and Morphological Reconstruction

Abstract: In low-pressure casting, aluminum alloy wheels are prone to internal defects such as gas holes and shrinkage cavities, which call for X-ray inspection to ensure quality. Automatic defect segmentation of X-ray images is an important task in X-ray inspection of wheels. For this, a solution is proposed here that combines adaptive threshold segmentation algorithm and mathematical morphology reconstruction. First, the X-ray image of the wheel is smoothed, and then the smoothed image is subtracted from the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The paper by Zhang et al [16] is concerned with a technical solution that combines the adaptive threshold segmentation algorithm and the morphological reconstruction operation to extract the defects on wheel X-ray images. The obtained results show that this method is capable of accurate segmentation of wheel hub defects.…”
Section: Nondestructive Testingmentioning
confidence: 99%
“…The paper by Zhang et al [16] is concerned with a technical solution that combines the adaptive threshold segmentation algorithm and the morphological reconstruction operation to extract the defects on wheel X-ray images. The obtained results show that this method is capable of accurate segmentation of wheel hub defects.…”
Section: Nondestructive Testingmentioning
confidence: 99%
“…References [36,37] indicated that gray-level morphological reconstruction (GMR) can be used to extract objects, which are connected components with the same intensity value and larger (smaller) than the intensity value of the external boundary pixels, while keeping their intensity, shape, and contour detail information and suppressing trivial background clutter and noise. Motivated by this vision, as analyzed in above Section 2.1 part, since the ship target is also a small uniform region with higher (lower) contrast compared with its surrounding backgrounds in TIR remote sensing image, we adopt morphological reconstruction [38] on gray-level infrared images in a dual method to highlight ship targets and remove sea clutter simultaneously.…”
Section: Pre-processing and Intensity Foreground Saliency Detectionmentioning
confidence: 99%
“…Many nondestructive testing methods are available, such as visual inspection [1,2], radiography [3], computed tomography [4], acoustic emission monitoring [5], ultrasound [1,6], and magnetic flux leakage [7]. However, many of these methods have limitations when applied to multi-wire cables.…”
Section: Introductionmentioning
confidence: 99%